Analisis Nilai-Nilai Pendidikan KArakter Pada Kumpulan Dongeng dan Cerita Rakyat Karya Ajeng Restiyani Serta Relevansinya Sebagai Buku Penunjang Bahasa Indonesia Kelas V di SD M 22 Sruni Surakarta Tahun 2015/2016 - Yunika, Fiviana; , Drs. Suwarno, SH., M. Pd (2016)
ABSTRACT Fiviana Yunika. NIM: A510120180. ANALYSIS IN THE VALUE OF CHARACTER EDUCATION IN THE COLLECTION OF FAIRY TALES AND FOLKLORE BY AJENG RESTIYANI AND RELEVANCE AS TEACHING MATERIALS INDONESIAN CLASS V IN PRIMARY SCHOOL M 22 SRUNI SURAKARTA. Essay. The Faculty of Education, University of Muhammadiyah Surakarta. The purpose of this study to describe the form in the value of character education in the collection of fairy tales and folklore by Ajeng Restiyani. To find relevance as teaching materials Indonesian class V in primary school M 22 Sruni Surakarta. This kind of research included in qualitative research methods of research librarian. Research librarian was conducted to analyze the content of the collection fairy tales and folklore by Ajeng Restiyani. Techniques of data throuh the interview method with teacher in class V about relevance as teaching materials Indonesian in primary school Muhammadiyah 22 Sruni Surakarta. Result of the research that the book fairy tales and folklore contains 18 educational value corresponding character compiled by The Agency Curriculum Development and Reserch Center. Result by interview and analysis of value character of the collection fairy tales and folklore by Ajeng Restiyani can relevance as teaching materials Indonesian in primary school Muhammadiyah 22 Sruni Surakarta for class V. Keywords: character building, folklore, teaching materials